When left does not seem right: epigenetic and bioelectric differences between left- and right-sided breast cancer. - Sofía, Masuelli.; Sebastián, Real.; Emanuel, Campoy.; Branham, María Teresita.; Marzese, Diego Matías.; Matthew, Salomon.; De Blas, Gerardo.; Rodolfo, Arias.; Michael, Levin.; María, Roqué. (Tufts University. Tisch Library., 2022)
Keywords: Asymmetry, Laterality, Left, Right, Breast cancer.; Springer Open.